2022
DOI: 10.1039/d2sc00737a
|View full text |Cite
|
Sign up to set email alerts
|

Advancing homogeneous catalysis for parahydrogen-derived hyperpolarisation and its NMR applications

Abstract: Parahydrogen-induced polarisation (PHIP) is a nuclear spin hyperpolaristion technique employed to enhance NMR signals for a wide range of molecules. This is achieved by exploiting chemical reactions of parahydrogen (para-H2),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 230 publications
2
48
1
Order By: Relevance
“…We believe that further development of metal-free imine hydrogenation can lead to much higher enhancements, ideally reaching the levels of metal-containing catalysts. Generally, this study shows that PHIP-assisted mechanistic studies provide important mechanistic information about metal-free hydrogenations, as proved many times similarly for metal-containing catalysts 19,20,45,46 and, in addition to this study, only once for a metal-free catalyst. 35…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We believe that further development of metal-free imine hydrogenation can lead to much higher enhancements, ideally reaching the levels of metal-containing catalysts. Generally, this study shows that PHIP-assisted mechanistic studies provide important mechanistic information about metal-free hydrogenations, as proved many times similarly for metal-containing catalysts 19,20,45,46 and, in addition to this study, only once for a metal-free catalyst. 35…”
Section: Discussionsupporting
confidence: 77%
“…Although PHIP was mostly used to study reactions mediated by metal-containing catalysts, 19,20,27,28 it was reported that metal-free catalysts can activate parahydrogen, leading to PHIP effects. 29,30 Specifically, AABs were the first FLPs to show spin hyperpolarization effects in reactions with parahydrogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHIP has been widely used to study mechanism in molecular homogeneous catalysis in solution, ,, and there is now a significant body of work dedicated to gas-phase PHIP using classical heterogeneous catalysts. , Our crystalline SMOM systems clearly establish a connection between molecular catalysis (rate, selectivity through precise ligand design, and atomic-level resolution of molecular structure) with heterogeneous systems (product/catalyst separation, stability, and recyclability). The highly active “single-site” nature of our SMOM system, and attendant high catalytic flux with retention of polarization in the products, also allows for the real-time interrogation of an evolving molecular heterogeneous catalyst system.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include MRI visualization of hydrogenation of propylene in a packed catalyst bed , or microchip reactors, hydrogenation of ethylene in a packed bed or in monolithic reactors, and CO 2 methanation . To minimize the distortion of the magnetic field, a glass tube model reactor with a thin layer of various catalytically active coatings was designed and implemented for spectroscopic and imaging experiments. , A significant improvement in NMR and MRI experiments can be achieved by using hyperpolarization of nuclear spins, which boosts signal intensity by up to several orders of magnitude and, consequently, provides an increase in the signal-to-noise ratio (SNR). An efficient and inexpensive hyperpolarization technique particularly suited for studies in heterogeneous catalysis is parahydrogen-induced polarization (PHIP). It is based on pairwise addition of the parahydrogen ( p -H 2 ) molecule to an unsaturated reactant (e.g., alkyne, alkene, etc.)…”
Section: Introductionmentioning
confidence: 99%